Krisis PPKM Darurat Di Pulau Jawa: Bagaimana Para Gubernur Mengkomunikasikannya Melalui Instagram - Muhibudin Wijaya Laksana (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2021)
In July 2021 the government issued a policy on the Implementation of Restrictions on Community Activities (PPKM) of the Java-Bali Emergency as a step in tackling the Covid-19 pandemic crisis in the Java region. This policy is specifically addressed to the governors in Java as instructions to be able to suppress the decline in the number of COVID-19 cases in their respective regions. The governors used Instagram as one of the channels in communicating the policy. The study aims to look at the comparison of crisis communication strategies carried out by governors through Instagram. The study is based on the Situational Crisis Communciation Theory (Timothy Coombs, 1995). Content Analysis is used as a tool to analyze the contents of the uploads of governors in java about emergency PPKM. The results of this study show that crisis communication conducted by governors has a different tendency to communicate the substance of policy.